2022
DOI: 10.1111/mam.12300
|View full text |Cite
|
Sign up to set email alerts
|

Middle‐out ecology: small carnivores as sentinels of global change

Abstract: Species that respond to ecosystem change in a timely, measurable, and interpretable way can be used as sentinels of global change. Contrary to a pervasive view, we suggest that, among Carnivora, small carnivores are more appropriate sentinels than large carnivores. This reasoning is built around six key points: that, compared to large carnivores, small carnivores 1) are more species-rich and diverse, providing more potential sentinels in many systems; 2) occupy a wider range of ecological niches, exhibiting a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 70 publications
0
28
0
Order By: Relevance
“…Indeed, recent studies on spotted skunks have shown their utility in advancing our understanding of disease outbreaks (Harris et al, 2021), historical climate and land use change (Cheeseman et al, 2021a(Cheeseman et al, , 2021b, changing predator community dynamics (Bolas et al, 2022), and food web linkages between aquatic, terrestrial and arboreal systems (Tosa et al, 2023). Such sensitivities by small carnivores are not unique to our system and are likely represented in small carnivores in ecosystems globally (Do Linh San et al, 2022;Marneweck, Allen, et al, 2022). Further, as highlighted in this study, efforts to develop novel monitoring strategies for small carnivores have provided data and unique insight into the full suite of carnivores within communities.…”
Section: F I G U R Ementioning
confidence: 99%
See 3 more Smart Citations
“…Indeed, recent studies on spotted skunks have shown their utility in advancing our understanding of disease outbreaks (Harris et al, 2021), historical climate and land use change (Cheeseman et al, 2021a(Cheeseman et al, , 2021b, changing predator community dynamics (Bolas et al, 2022), and food web linkages between aquatic, terrestrial and arboreal systems (Tosa et al, 2023). Such sensitivities by small carnivores are not unique to our system and are likely represented in small carnivores in ecosystems globally (Do Linh San et al, 2022;Marneweck, Allen, et al, 2022). Further, as highlighted in this study, efforts to develop novel monitoring strategies for small carnivores have provided data and unique insight into the full suite of carnivores within communities.…”
Section: F I G U R Ementioning
confidence: 99%
“…Large apex carnivores can have well‐documented impacts on the abundance and behaviour of large herbivore prey, which have been shown to have cascading impacts on lower trophic levels and broader ecological processes (Ripple et al, 2014). While less popularized, small or medium‐sized carnivores (<16 kg) that typically occupy lower trophic levels within carnivore communities, account for 89% of all terrestrial carnivore species and can impact ecosystems in a variety of ways—ranging from predation of herbivores to seed dispersal (Do Linh San et al, 2022; Marneweck, Allen, et al, 2022). The ecological niches occupied by carnivores can change based on the presence of other carnivores, and alter their behaviour and abundance (and thus ecological impact) depending on the presence or absence of larger carnivores in a system (Linnell & Strand, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The leopard cat, Prionailurus bengalensis from Family Felidae, is a typically nocturnal mesopredator in many temperate and (sub-)tropical forest ecosystems across most parts of Asia [ 19 ]. This cat can serve as an indicator species to prioritize conservation planning [ 20 ], due to the continued population decline as a result of habitat loss and illegal hunting [ 21 , 22 ]. This cat often uses opportunistic feeding strategies and exhibits plasticity in its habitat use and temporal activity to accommodate to habitat modification.…”
Section: Introductionmentioning
confidence: 99%